Mammalian tRNA acetylation determines translation efficiency and tRNA quality control - Na Liu; Bingxue Liu; Chun-Rui Ma; Zixin Cai; Jin-Tao Wang; Zi-Qing Chai; Nanlin Zhu; Ting Shao; Yue-Lei Chen; Yu Lin; Yirong Wang; Hong Xu; et al. (Nature Communications)
Abstract Acetylation is a conserved and pivotal RNA modification. Acetylation of tRNA occurs at C12 (ac4C12) in eukaryotic tRNAs. Yeast ac4C12 prevents tRNASer from rapid tRNA decay (RTD) at higher temperatures. However, the biological function of ac4C12 in higher eukaryotes remains unexplored. Moreover, whether mammalian cells contain an RTD pathway is unclear. Here, we deleted Thumpd1, the indispensable factor for ac4C12 biogenesis, in NIH/3T3 cells. Loss of ac4C12 significantly reduced tRNA aminoacylation and translational efficiency physiologically, in particular, of those enriched with Ser/Leu codons with two U/A nucleotides. Remarkably, ac4C12 hypomodification selectively generated rapid tRNALeu(CAG) turnover under heat stress. We demonstrated that tRNALeu(CAG) was degraded by a mammalian RTD (mRTD) mechanism, consisting of Xrn1/Xrn2-mediated 5’−3’ exonuclease digestion and intracellular pAp level control by Bpnt1/Bpnt2. Our results reveal both the pivotal roles of ac4C12 in translation and a mRTD pathway for tRNA quality control under heat stress in mammalian cells.